1993
DOI: 10.1590/s0036-46651993000200001
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system involvement in Chagas' disease: an updating

Abstract: A review was made of the available literature on central nervous system (CNS) involvement in Chagas' disease. Thirty-one works concerning the acute nervous form and 17 others dealing with the chronic nervous form, all presenting neuropathologic studies, were critically analysed. Based on this analysis, an attempt was made to establish the possible natural history of CNS involvement in Chagas' disease. Among others, the following facts stand out: 1) the initial, acute phase of Trypanosoma cruzi infection is usu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
4

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 22 publications
0
46
0
4
Order By: Relevance
“…It is also possible that the cerebral lesions are indeed related to reactivation instead of being present prior to the immunosuppression. According to Pittella (1993), symptomatic acute forms accompanied by chagasic encephalitis are grave with death in virtually all cases and reactivation of the CNS infection in the chronic form of Chagas' disease occurs only in immunosuppressed patients. The parasite kDNA restriction pattern detected can be used as a marker for further comparisons with other T. cruzi strains from immunosuppressed and immunocompetent patients from the same and other endemic areas (Pacheco et al unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that the cerebral lesions are indeed related to reactivation instead of being present prior to the immunosuppression. According to Pittella (1993), symptomatic acute forms accompanied by chagasic encephalitis are grave with death in virtually all cases and reactivation of the CNS infection in the chronic form of Chagas' disease occurs only in immunosuppressed patients. The parasite kDNA restriction pattern detected can be used as a marker for further comparisons with other T. cruzi strains from immunosuppressed and immunocompetent patients from the same and other endemic areas (Pacheco et al unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the clinical condition refers to the place of the reactivation. Therefore, the neurological condition draws more the attention 25,52,65,66,87 that in most of the times has toxoplasmosis as the main diagnosis in view to the frequency that this condition happens in HIV infected individuals 33,37,68 . In the heart, the symptomatology and the physical aspects overlap those seen on the natural evolution of the chronic chagasic cardiopathy, hindering the diagnosis 22,27,34,42,88 .…”
Section: Casesmentioning
confidence: 99%
“…Particularly in cases of HIV co-infection the clinical symptoms are frequently peculiar. Cases of central nervous system tumor-like lesions (Ferreira et al 1991, Pittella 1993, Rocha et al 1994) and cutaneous lesions manifestations (Amato et al 1997) related to the reactivation of Chagas' disease have been reported in association with immunosuppression. Distinct Leishmania isoenzymatic patterns and specific dermotropic zymodemes have also been found causing visceral leishmaniasis (Campino et al 1994, Jimenez et al 1995, Alvar et al 1997.…”
mentioning
confidence: 99%